Źródła i instrumenty konkurencyjności średnich przedsiębiorstw - Nogalski, Bogdan; Wójcik-Karpacz, Anna; Karpacz, Jarosław (Sources and instruments of competitiveness of medium-sized enterprises, 2006)
The paper is an attempt to identify sources and instruments of competitiveness of medium sized enterprises in Poland. The analysis based on literature research was enriched by results of research conducted among entrepreneurs of medium-sized companies in Świętokrzyski region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 236-246